Monetary Policy Normals, Future and Past. (August 2017) - Sinclair, Peter; Allen, William A.
Abstract : The paper looks at the 'new normal' in so many of the world's central banks, and specifically the UK. It examines the position of the monetary policy framework, instrument settings, the underlying models, unconventional policy measures, real interest rates, and the interface with macroprudential policy. It explores both the advantages and challenges involved in any move to return towards pre-crisis arrangements, and offers suggestions for possible ways in which current policy dilemmas might be resolved.